Natural convection heat transfer in PCM suspensions in a square enclosure with bottom heating and top cooling. (1st October 2021) - Ho, C.J.; Jang, C.; Lai, Chi-Ming
Highlights: Natural convection in an enclosure with PCM suspension was numerically investigated. Enclosure bottom and top are isothermal heating and cooling respectively. Transient and steady-state natural convection are considered. All the parameters ( R a T, Ste, Sb, and c m, i ) affect the flow pattern. Heat flow oscillations occur at Sb  = 0.5–1. Abstract: Research on the use of phase change material (PCM) suspensions to improve the natural convection efficiency of thermal systems is booming; however, there are few studies on the transient behavior of PCM suspensions. In this study, numerical simulations were used to investigate transient and steady-state natural convection in a square enclosure containing a PCM suspension. The implicit finite-difference method was adopted. The left and right walls of the enclosure were adiabatic sections, the bottom was an isothermal heating, and the top was an isothermal cooling. The following parameters were considered: PCM = n-octadecane (C18 H38 ), enclosure aspect ratio = 1, buoyancy ratio for mass-to-heat transfer = 1, Rayleigh number ( R a T ) = 10 3 –10 4, Stefan number ( Ste ) = 0.005–0.05, subcooling factor ( Sb ) = 0–10, and initial mass fraction ( c m, i ) = 0–20%. The results show that all the parameters ( R a T, Ste, Sb, and c m, i ) affect the flow pattern, and convection oscillations occur at Sb  = 0.5–1. The heat transfer rate increases with R a T . Both c m, i and Sb affect the heat transfer rate but in a case-specific manner, and no well-defined correlations are observed.